Evaluation of a 3D Solution Space-based ATC Workload Metric. Issue 19 (2019) - Somers, V.L.J.; Borst, C.; Mulder, Max; van Paassen, M.M.
Abstract: Air Traffic Control (ATC) workload is a limiting factor for air traffic growth, creating a need for objective ATC workload metrics. Previous research has shown that the solution space diagram can be a basis for a workload prediction metric. The current solution space metric however, does not incorporate altitude. In this paper, a 3D solution space metric is described and evaluated. An experiment has been conducted to test the relation of the 3D solution space metric with workload and compare it to other workload metrics; the aircraft count, and a quasi-3D metric: the 2D layered solution space and the Instantaneous Self Assessment-based method. Weak correlations with workload were found for all tested metrics and no significant differences were found between them. Although no significant differences were found, the 2D layered metric showed better results than the 3D solution space-based metric, indicating that air traffic controllers might think in 2D layers over fixed altitude ranges rather than considering the complete 3D physical solution space.